THE EFFECT OF DIFFERENT CONCENTRATIONS OF STARFRUIT ACIDS WULUH (Averrhoa bilimbi L) ON MINERAL EXTRACTION OF VANNAME SHRIMP SHELL (Litopenaeusvannamei) - Gianthi, Fiskia; Karnila, Rahman; Ilza, Mirna (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
AbstractShrimp waste flour is a waste product containing fairly good nutrient, those are crude protein between 35 to 45% and minerals (calcium, phosphorus and magnesium). The organic acid contained in star fruit can be used as a solvent for mineral extraction. This study was aimed to determine whether starfruit acid with different concentrations could extract the minerals contained in vanname shrimp shell flour. This research was carried out in several stages such as sample preparation, different concentrations treatment, testing the chemical composition and extracting the minerals calcium, magnesium and phosphorus. The results of this study indicate that the highest concentration of 20% starfruit acid was showing the higher value of mineral extraction than the concentration of 10% and 15%. The shrimp shell flour was containing calcium 5.75 mg/kg, magnesium 0.653 mg/kg, and phosphorus 0.223 mg/kg. Keywords:Vannamei Shrimp, Extraction, Mineral.